2003
DOI: 10.1088/0022-3727/36/6/101
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Zn nanofibres through simple thermal vapour-phase deposition

Abstract: Zn nanowires and nanoribbons have been synthesized from Zn powders through a simple thermal-vapour deposition process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…This hypothesis is supported by findings recently published for Zn nanofibers prepared by evaporation of Zn powder. [37] The TEM image ( Figure 3 d) also shows the presence of agglomerated particles with lower contrast. EDX measurements on these agglomerated particles indicate a 1:1 atomic ratio of zinc and oxygen.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This hypothesis is supported by findings recently published for Zn nanofibers prepared by evaporation of Zn powder. [37] The TEM image ( Figure 3 d) also shows the presence of agglomerated particles with lower contrast. EDX measurements on these agglomerated particles indicate a 1:1 atomic ratio of zinc and oxygen.…”
Section: Resultsmentioning
confidence: 93%
“…To the best of our knowledge there is as yet no report on the formation of "Zn whiskers" at such a low temperature. [37] It can be suggested that the Zn whiskers grow by a vapor-solid (VS) mechanism caused by the high volatility of elemental zinc. This hypothesis is supported by findings recently published for Zn nanofibers prepared by evaporation of Zn powder.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, since there is no catalyst particle at the tips of the nanowires, these Zn nanowires should be formed via a vapor-solid (VS) mechanism [31]. It is clear that the ball milling treatment of the starting materials enhances the nanowire formation in both density and quantity, which could be associated with a faster reaction between B and ZnO, as well as a reduced reaction temperature.…”
Section: Zn Nanowiresmentioning
confidence: 99%
“…Of the various physical and chemical methods, radiation chemistry, laser ablation technique [11], thermal evaporation [12][13][14], biosynthesis [15,16], and electrodeposition [17][18][19][20][21] are often used to synthesise zinc nanostructures. Of all the methodologies developed for the preparation of Zn NPs, the electrochemical method (bottom-up approach) offers a simple alternative mean for high yield of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%